Analisis Bentuk Nilai-Nilai Cinta Kasih Dalam Novel Sabtu Bersama Bapak Karya Adhitya Mulya - Sinaga, Wahyu Ananda; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2024)
Research analyzing the values of love in novels is an important study that must be studied. This study aims to examine the various forms of love values in the novel Sabtu Bersama Bapak by Adhitya Mulya. The method used in this research is descriptive qualitative, where the data obtained in the form of character quotes (words, phrases, clauses, and sentences) and narrators in the novel that show the action of the form of love values. The data collected is analyzed by steps, namely (1) Describing or marking quotations related to the value of love in the novel, (2) Organizing data by recording quotations, (3) Explaining conclusions from all data obtained. Based on the data analysis, the forms of the value of love contained in the novel under study are (1) Love for God (Agapei), (2) Love for Family (Storge), (3) Love for Friends (Philia), (4) Romantic Love (Eros).